2008
DOI: 10.1063/1.2830555
|View full text |Cite
|
Sign up to set email alerts
|

Nature of magnetism in copper-doped oxides: ZrO2, TiO2, MgO, SiO2, Al2O3, and ZnO

Abstract: The nature of magnetism in 10% Cu-doped ZrO2, TiO2, MgO, SiO2, and Al2O3 is investigated using superconducting quantum interference device magnetometry and electron magnetic resonance (EMR). The doping was done by the incipient wetness impregnation technique. X-ray diffraction studies showed the presence of some CuO notably in TiO2, SiO2, and Al2O3. However, EMR yielded typical Cu2+ spectra in all the samples, resulting from some doping. Magnetic field (H) and temperature (T) dependences of the magnetization (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…This development rooted back in 1998 when Ohno et al [1] reported the existence of ferromagnetism in Mndoped GaAs at a temperature greater than 100 K. Earlier metal oxides like TiO 2 [2], ZnO [2], SnO 2 [3], and In 2 O 3 [2] were doped with transition metals (TM) such as Co [4,5], Mn [6], Fe [7], Cu [8,9], Ti [10], and V [10] and also surface functionalized with organic molecules [11] to create high-moment DMS materials. Among metal oxides, ZnO is widely used in optoelectronic and spintronic applications [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This development rooted back in 1998 when Ohno et al [1] reported the existence of ferromagnetism in Mndoped GaAs at a temperature greater than 100 K. Earlier metal oxides like TiO 2 [2], ZnO [2], SnO 2 [3], and In 2 O 3 [2] were doped with transition metals (TM) such as Co [4,5], Mn [6], Fe [7], Cu [8,9], Ti [10], and V [10] and also surface functionalized with organic molecules [11] to create high-moment DMS materials. Among metal oxides, ZnO is widely used in optoelectronic and spintronic applications [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic FM is often controversial and difficult to be stabilized or controlled. It strongly depends on the sample history; samples grown under similar conditions may exhibit different magnetic properties [12]. Until now, there is no clear consensus on the mechanism of the observed unexpected d 0 magnetism.…”
mentioning
confidence: 99%
“…(3) Cu. ZnO doped with Cu has been proven to possess ferromagnetism and it is well studied [9]. Here, we only concentrate on the first two groups.…”
Section: Resultsmentioning
confidence: 99%